Extreme weather events drastically reduce school completion by Mongolian children - Kati Kraehnert; Valeria Groppo (DIW Weekly Report, 2018)
As climate change progresses, extreme weather events are occurring more often, with developing countries suffering the brunt. Using Mongolia as an example, this study examines how extremely cold and snowy winters-which lead to high livestock mortality and thus threaten the livelihood of many households-impact children's school completion. The results, based on a representative household survey conducted by DIW Berlin and the Mongolian National Statistical Office, show that Mongolian children who experienced an extreme winter while of schooling age and lived in a severely affected district had a 20.1 to 26.1 percentage point lower probability of completing the nine years of mandatory education compared to their peers in unaffected areas. As education is a significant determinant of an individual's income, extreme weather events are likely to have long-lasting consequences for the children examined in this study. Policymakers should therefore implement support measures, including emergency aid, to enable children in affected households to attend school without interruption and complete their education.
Keywords: O12; 330; children; education; extreme weather events; Mongolia